2018
DOI: 10.1080/14647273.2018.1456682
|View full text |Cite
|
Sign up to set email alerts
|

Telomeres as a molecular marker of male infertility

Abstract: In recent years, male infertility has become a growing social problem. Standard diagnostic procedures, based on assessing seminological parameters, are often insufficient to explain the causes of male infertility. Because of this, new markers with better clinical application are being sought. One of the promising markers seems to be an assessment of telomere length of sperm. Sperm telomeres, in contrast to somatic cells, are elongated as men age. The results of some studies suggest that telomere length may be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 87 publications
0
16
0
Order By: Relevance
“…21 Therefore, STL measurement is suggested to predict clinical outcomes. 22 Several studies have demonstrated an impact of lifestyle factors on telomere lengths, mainly in leucocytes (for reviews, see. 23 Lifestyle factors have also been stated to potentially affect sperm quality and fertility.…”
Section: Introductionmentioning
confidence: 99%
“…21 Therefore, STL measurement is suggested to predict clinical outcomes. 22 Several studies have demonstrated an impact of lifestyle factors on telomere lengths, mainly in leucocytes (for reviews, see. 23 Lifestyle factors have also been stated to potentially affect sperm quality and fertility.…”
Section: Introductionmentioning
confidence: 99%
“…This is probably the reason why the aforementioned associations were not observed and STL in patients with normozoospermia was lower than in patients with abnormal semen parameters. In fact, the demonstration that STL is an additional sperm parameter may open new perspectives in the evaluation of infertile males [31,32]. Additional research on men of proven fertility and infertility will clarify the significance of this biomarker also as a quality parameter for semen.…”
Section: Discussionmentioning
confidence: 97%
“…For example, sperm telomeres have been reported to both decline [91] and increase [101] with male age in mice Mus musculus, but decrease in rats Rattus norvegicus [104]. In humans, telomere lengths in sperm have been found to increase with male age [92,105] in contrast to the pattern in somatic tissues [106]. How an increase with male age occurs remains unclear [106].…”
Section: (B) Telomere Attrition In the Germlinementioning
confidence: 99%
“…In humans, telomere lengths in sperm have been found to increase with male age [92,105] in contrast to the pattern in somatic tissues [106]. How an increase with male age occurs remains unclear [106]. It could be due to expression of telomerase, or stringent quality control of sperm that results in the removal of an increasing proportion of sperm with short telomeres as males age, or be a consequence of cohort effects or differential survival of male phenotypes [106].…”
Section: (B) Telomere Attrition In the Germlinementioning
confidence: 99%